INCULCATION ENTREPRENEURSHIP VALUES IN EARLY CHILDHOOD THROUGH PROJECT METHOD (Classroom Action Research in Children Class B2 RA Miftahul Falah Cileunyi-Bandung) - Syifauzakia Syifauzakia (Tunas Siliwangi, 2016)
This study is the embodiment of one of the Ministry of National Education program on the development ofentrepreneurship education the integration of entrepreneurship education with character education in theeducational unit by developing the entrepreneurship values. The reason this research conducted becauseaccording to the results of preliminary studies inculcation of entrepreneurship values in RA Miftahul Falahhas not run optimally. The core objective of this study was to inculcate the values of entrepreneurship inearly childhood through the project method. This research used methods of action research conductedcollaboratively in four cycles over two months. Data collection tools in this study include observationthrough field notes, interviews, and documentation. After inculcating entrepreneurship values in earlychildhood through project method in class B2 RA Miftahul Falah there are 11 values that arise from childare: (1) autonomy; (2) creative; (3) dare to take risk; (4) action oriented; (5) leadership; (6) hard work; (7) discipline; (8) responsible; (9) cooperation; (10) curiosity; (11) communicative. As for the supporting factors in this research are: (1) media; (2) teacher strategies in learning; (3) cooperation between teacher and writer; (4) interesting learning process and direct practice; (5) peer influence.Key Word: Entrepreneurship Values, Early Childhood, Project Method